(untitled) (The Geographic Base, 2021)
As conventional non-renewable energy is becoming increasingly scarce, the development of renewable energies, such as solar energy, has become a major priority in today’s world. In this study, it has developed an approach to simulate solar radiation on rooftops of Paschimanchal Campus and estimate the solar photovoltaic (PV) potential using Photogrammetry and GIS techniques. The object-based method was used to extract and classify buildings using very high-resolution data: orthophoto, the UAV-derived Digital Surface Model, and Digital Terrain Model raster layers. For more accurate estimation of solar panel installations, the evaluation of solar radiation is essential and the amount of solar radiation that was converted into solar PV potential depends upon the technical characteristics of the panel (technology used: monocrystalline or polycrystalline). Subsequently, the evaluated cost of solar panel installation was compared to the cost of grid-based electricity of the study area. The result obtained shows that 18 rooftops of the buildings are the most suitable place for solar panel installation and their usable area is 4303.67m². 32 For polycrystalline and monocrystalline technologies, the annual PV power generation in the study area is 868 MWh/ yr and 1274 MWh/yr respectively. It was found that 1428.42m² of the suitable area was enough to fulfill the yearly demand of Paschimanchal Campus. For polycrystalline technologies, around 876 panels costing NRS.1,57,68,000 are required. The cost analysis of 10 years concludes solar energy will be cheaper than grid-based electricity by NRS.1,04,10,785.